Respuesta :
Answer:
all x intercepts [-4, 0] [4, 0]
Step-by-step explanation:
x-intercept, i.e. y=0
f(x) = x^3 - 4x^2 - 16x + 64 = 0
(x^3 + 4^3) - 4x^2 - 16x = 0 [FYI, x^3 + y^3 = (x + y)(x^2 - xy + y^2)]
(x + 4)(x^2 - 4x + 16) - 4x^2 - 16x = 0
(x + 4)(x^2 - 4x + 16) - 4x(x + 4) = 0
(x + 4)(x^2 - 4x + 16 - 4x) = 0
(x + 4)(x^2 - 8x + 16) = 0
(x + 4)(x - 4)^2 = 0
x = -4 or 4
all x intercepts [-4, 0] [4, 0]
Step-by-step explanation:
one thing immediately catches the eye : the factors of the terms in the function follow the powers of 4 :
4⁰, 4¹, 4², 4³
and they are going against the powers of x :
x³ has the factor 4⁰
x² has the factor 4¹
x has the factor 4²
x⁰ has the factor 4³
with that we see that one 0 solution (an x- intercept) is x = 4.
f(4) = 4³ - 4×4² - 4²×4 + 4³ = 4³ - 4³ - 4³ + 4³ = 0
so, the functional expression is
(x-4)(x² + ...)
the other 2 zero solutions are covered by the quadratic term.
to get the quadratic term we divide f(x) by (x-4).
x³ - 4x² - 16x + 64 ÷ x - 4 = x² - 16
- x³ - 4x²
-----------------------------
0 0 - 16x + 64
- - 16x + 64
----------------------‐--------
0 0
so,
f(x) = (x - 4)(x² - 16)
and as we know
(a² - b²) = (a + b)(a - b)
we get
f(x) = (x - 4)(x + 4)(x - 4) = (x - 4)²(x + 4)
so, x = 4 counts as 2 zero solutions, it is a point, where the curve makes a turn and only touches the x-axis, but does not fully intercept it (in the sense to continue on the other side of the x-axis).
and x = -4 is the third zero solution.
so, the x-intercepts are at x = -4, +4